Selected writings and speeches of Marcus Garvey - Garvey, Marcus (Mineola, N.Y Dover Publications, 2004)
A controversial figure in the history of race relations around the world, Marcus Garvey amazed his enemies as much as he dazzled his admirers. This anthology contains some of the African-American rights advocate's most noted writings and speeches, including "Declaration of the Rights of the Negro Peoples of the World" and "Africa for the Africans."
Includes bibliographical references.
Keywords: Garvey, Marcus, 1887-1940.